FORSTERITE SURFACE COMPOSITION IN AQUEOUS SOLUTIONS: A COMBINED POTENTIOMETRIC, ELECTROKINETIC, AND SPECTROSCOPIC APPROACH - Pokrovsky O.S.; Schott J. (My University, 2000)
Surfaces of natural and synthetic forsterite (Fo91 and Fo100) in aqueous solutions at 25°C were investigated using surface titrations in batch and limited residence time reactors, column filtration experiments, electrokinetic measurements (streaming potential and electrophoresis techniques), Diffuse Reflectance Infrared Spectroscopy (DRIFT), and X-ray Photoelectron Spectroscopy (XPS). At pH < 9, a Mg-depleted, Si-rich layer (<20 #9 thick) is formed on the forsterite surface due to a mg2+ # H+ exchange reaction. Electrokinetic measurements yield a pHIEP value of 4.5 corresponding to the dominance of SiO2 in the surface layer at pH < 9. In contrast, surface titrations of fresh powders give an apparent pHPZC of about 10 with the development of a large positive charge (up to 10-4 mol/m2 or 10 C/m2) in the acid pH region. This may be explained by penetration of H+ into the first unit cells of forsterite surface. The surface charge of acid-reacted forsterite is one or two orders of magnitude lower than that of unreacted forsterite with an apparent pHPZC at around 6.5 and a pHIEP value of 2.1 which is close to that for amorphous silica and reflects the formation of a silica-rich layer on the surface. XPS analyses indicate the penetration of hydrogen into the surface and the polymerization of silica tetrahedra in this leached layer. At pH > 10, a Si-deficient, Mg-rich surface layer is formed as shown by XPS analyses and the preferential Si release from the surface during column filtration experiments.